2017
DOI: 10.1016/j.math.2016.10.066
|View full text |Cite
|
Sign up to set email alerts
|

Clinical prediction rules for prognosis and treatment prescription in neck pain: A systematic review

Abstract: Clinical prediction rules (CPRs) developed to identify sub-groups of people with neck pain for different prognoses (i.e. prognostic) or response to treatments (i.e. prescriptive) have been recommended as a research priority to improve health outcomes for these conditions. A systematic review was undertaken to identify prognostic and prescriptive CPRs relevant to the conservative management of adults with neck pain and to appraise stage of development, quality and readiness for clinical application. Six databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 71 publications
3
28
0
Order By: Relevance
“…Standard post-surgical rehabilitation (weeks [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Participants in this group were treated in accordance with the Swedish standard post-surgical care of individuals with CR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Standard post-surgical rehabilitation (weeks [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Participants in this group were treated in accordance with the Swedish standard post-surgical care of individuals with CR.…”
Section: Resultsmentioning
confidence: 99%
“…Prognostic models play an important role not only in the clinical prediction of future health outcomes, but also identifying the most influential predictors that could inform either clinical management or lead to the development of novel therapeutic interventions 6 . Compared to other musculoskeletal disorders such as low back pain (LBP) and idiopathic neck pain (NP) 7 – 9 , there is comparatively fewer prognostic studies in the area of CR 10 , 11 . Current prognostic studies in CR have focused largely either on self-reported predictors 11 , 12 , or on objective physical measures 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For whiplash-associated disorders, a tool predicting both chronic disability and full recovery has been developed [ 51 , 52 ]. For neck pain however, current evidence does not support clinical use of neither prognostic nor prescriptive clinical prediction rules [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The quality of the available evidence was graded as low to very low and included only a few modifiable factors. Psychosocial factors as passive coping, catastrophizing, fear-avoidance beliefs, depressive symptoms, distress, and anxiety are potentially modifiable factors that were found to be associated with chronic neck pain, whiplash related neck pain, and low back pain [ 9 19 ]. These findings concern other subgroups of musculoskeletal pain, and can therefore not be generalized to patients with idiopathic nonspecific, non-traumatic, acute or subacute neck pain.…”
Section: Introductionmentioning
confidence: 99%